The relation between vaccination status and referral to a consultation–liaison psychiatry service for hospitalized patients with COVID-19 - Tomoe Nishihara; Mao Shibata; Ayako Ohashi; Kazutoshi Hiyama; Takafumi Yamashita; Mika Kuroiwa; Nobuyuki Sudo (BioPsychoSocial Medicine, 2023)
Abstract Background Previous studies have shown that patients with Coronavirus Disease 2019 (COVID-19) are likely to be affected by delirium and other psychiatric complications. We aimed to evaluate the relation between COVID-19 vaccination status and referral of patients hospitalized with COVID-19 for consultation–liaison psychiatry services. Method From the medical records used for this retrospective, single hospital-based study, 576 patients were identified who were over 18 years-of-age and hospitalized with a diagnosis of COVID-19 between March 2020 and March 2022. The data of 531 for whom the vaccine history was obtained from the medical records were available for analysis: 455 without and 76 with referral to consultation–liaison psychiatry. A history of COVID-19 vaccination at least two times was used in the analysis of the odds for referral to liaison psychiatric consultation: 95% confidence interval (CI) in multivariable logistic regression. The adjustment factors included sex, age, body mass index (BMI), severity of COVID-19, C-reactive protein level, medical history, and therapeutic factors such as the use of remdesivir, steroids, or mechanical ventilation. Results The prevalence of psychiatric consultation was 14.3%. Patients without vaccination had a 7-times greater OR (95%CI:2.08–23.58) than vaccinated patients for a referral for consultation–liaison psychiatry services after adjusting for confounding factors. Conclusion Non-vaccination was associated with a greater likelihood of referral for consultation–liaison psychiatry service among these hospitalized Japanese patients with COVID-19, even after adjusting for clinical and therapeutic factors. It is possible that vaccination greatly lessens the need for the referral of COVID-19 patients for consultation–liaison psychiatry services.